Transmigration program has been done for many years. However, many transmigration sites are identified as underdeveloped, especially in upland farm transmigration site laboured with food crops. The main constraint for such development relates with the limit of upland resource in supporting plant growth. The upland resources is generally marginal in physical properties (undulating, wavy and hilly topography); the poor quality in land clearing which cause removal upper layer and loss of organic ma - Benar Darius Ginting; Muhammad Syamsul Maarif; Surjono H. Sutjahjo; Hermanto Siregar (Forum Pasca Sarjana, 2008)
Transmigration program has been done for many years. However, many transmigration sites are identified as underdeveloped, especially in upland farm transmigration site laboured with food crops. The main constraint for such development relates with the limit of upland resource in supporting plant growth. The upland resources is generally marginal in physical properties (undulating, wavy and hilly topography); the poor quality in land clearing which cause removal upper layer and loss of organic matter; relatively high rainfall intensity which causes the high erosivity. Such degradation has caused accumulation of problem for farmer. This research in erosion is done in order to know the strategy needed to be done. This research is done in Rantau Pandan SP 1 as case study. Several methods have been applied to determine 1) the amount of erosions 2) the permissible erosion, 3) the spatial pattern of erosion,and 4) the soil conservation action.   Key words: upland farming system, erosion, conservation